Dispatcher instruction of chest compression-only CPR increases actual provision of bystander CPR - Shimamoto, Tomonari; Iwami, Taku; Kitamura, Tetsuhisa; Nishiyama, Chika; Sakai, Tomohiko; Nishiuchi, Tatsuya; Hayashi, Yasuyuki; Kawamura, Takashi (Resuscitation, 2015)
A preceding randomized controlled trial demonstrated that chest compression-only cardiopulmonary resuscitation (CPR) instruction by dispatcher was more effective to increase bystander CPR than conventional CPR instruction. However, the actual condition of implementation of each type of dispatcher instruction (chest compression-only CPR [CCCPR] or conventional CPR with rescue breathing) and provision of bystander CPR in real prehospital settings has not been sufficiently investigated. This registry prospectively enrolled patients aged =>18 years suffering an out-of-hospital cardiac arrest (OHCA) of non-traumatic causes before emergency-medical-service (EMS) arrival, who were considered as target subjects of dispatcher instruction, resuscitated by EMS personnel, and transported to medical institutions in Osaka, Japan from January 2005 through December 2012. The primary outcome measure was provision of CPR by a bystander. Multiple logistic regression analysis was used to assess factors that were potentially associated with provision of bystander CPR. Among 37,283 target subjects of dispatcher instruction, 5743 received CCCPR instruction and 13,926 received conventional CPR instruction. The proportion of CCCPR instruction increased from 5.7% in 2005 to 25.6% in 2012 (p for trend <0.001). The CCCPR instruction group received bystander CPR more frequently than conventional CPR instruction group (70.0% versus 62.1%, p<0.001). In the multivariable analysis, CCCPR dispatcher instruction was significantly associated with provision of bystander CPR compared with conventional CPR instruction (adjusted odds ratio 1.44, 95% CI 1.34–1.55). CCCPR dispatcher instruction among adult OHCA patients significantly increased the actual provision of bystander CPR.